RELATIONSHIP SOCIAL SUPPORT AND RESILIENCE WITH STRESS LEVELS OF FAMILY CAREGIVERS HEMODIALYSIS PATIENTS SURABAYA - A Fahmil Haq Aplizuddin; Harmayetty Harmayetty; Elida Ulfiana (Critical Medical and Surgical Nursing Journal (CMSNJ), 2020)
Introduction: Hemodialysis is a life-long treatment for end-stage renal disease (ESRD). ESRD has physical and psychosocial challenges to experience stress which not only affects but patients but also family members who care for them or also called family caregivers. Analyzing the relationship of social support and resilience to the level of stress in the family caregiver of hemodialysis patients at Haji Hospital Surabaya.Methods: A cross-sectional study with a population of family caregiver members of hemodialysis patients at RSU Haji Surabaya. The sample size was 92 respondents with criteria, namely families who treat hemodialysis patients at RSU Haji Surabaya, live in one house with patients, aged > 18 years, and can read and write. The variables of this study are social support, resilience, and stress levels. Data collection was performed using a questionnaire and analyzed using Spearman’s Rho test. Results : There was a significant negative relationship between social support and stress levels (p = 0.004 and r = -0.296) and resiliency with stress levels (p = 0.003 and r = -0.311).Discussion: The level of stress in a family caregiver hemodialysis patient can be influenced by the social support received and the level of resilience they have. The social support has an important role for family caregivers obtained from the family and significant other.